Consumer education in foods for adults, based upon food buying methods of women in Fond du Lac, Wisconsin - Giuliani, Clara Eilert, author; Morgan, David H., advisor; Williamson, Maude, committee member; Elliff, Rowan, committee member; Betts, Gilbert L. (Gilbert Lee), 1893-1972, committee member (Colorado State University. Libraries, 1942)
To view the abstract, please see the full text of the document.
Keywords: Consumption (Economics); Purchasing